Theoretical Analysis of the Optical Response of Silicon/Silica/Gold Multishell Nanoparticles in Biological Tissue - Wajdi Chaabani; Abdallah Chehaidar; Julien Proust; Jérôme Plain (Advances in Materials Science and Engineering)
The scattering and absorption efficiencies of light by a single silicon/silica/gold spherical multishell in biological tissues are analyzed theoretically in the framework of Lorenz–Mie theory and finite-difference time-domain formalism. We first revised the ideal case of a concentric silicon/gold nanoshell, analyzed the effect of growing a silica layer of uniform thickness around the silicon core, and then examined the effect of an offset of the gold shell with respect to the centre of the silicon/silica nanoshell. Our simulation showed that the silicon/gold nanoshell in the biological tissue supports significant absorption and scattering resonances in the biological spectral window. On the contrary, the growth of a silica layer on the silicon core surface leads to a blueshift of these resonances accompanied by a slight increase of their magnitudes. The offset of the gold shell with respect to the silicon/silica core results in a redshift of the absorption and scattering resonances supported by the concentric silicon/silica/gold multishell within the biological window, accompanied by a decrease in their amplitudes. On the contrary, the gold shell offset gives rise to a more prominent electric field enhancement at the silicon/silica/gold multishell-biological tissue interface. Our simulation thus shows that silicon/silica/gold multishell nanoparticles are potential candidates in bioimaging and photothermal therapy applications.